Students’ Perceptions Towards Usage of ChatGPT among University Students - Haslindar Binti Ibrahim; Rudresh Pandey; Nureen Waheda binti Mohd Nazdir; Nureen Mirza binti Taharazwan; Riya Gupta; Nurazra Zafirah binti Suhaimi; Nurin Qasrina binti Nordin; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2026)
This study aims to explore students' perceptions towards usage of ChatGPT in higher education, focusing on how different aspects of the tool influence their attitudes and engagement. The independent variable consists of seven aspects of ChatGPT, which are capabilities, regulations and ethical concerns, satisfaction and attitude, study issues and outcomes, skills development, labor market and skill mismatch, and emotions, while the dependent variable is the overall usage of ChatGPT among university students. A quantitative research method was adopted using an online survey distributed through Google Forms to collect data from university students. The findings indicate that most students hold positive perceptions towards ChatGPT, viewing it as a useful tool for enhancing learning efficiency, developing new skills, and supporting academic tasks. However, some concerns remain regarding ethical use and overreliance on AI-generated content. The study concludes that ChatGPT has significant potential to complement traditional learning methods, provided it is used responsibly. The findings offer valuable implications for educators and policymakers in integrating AI tools effectively into educational settings.